Cover Image. (7th June 2021) - Kawai, Tatsuya; Brender, Jeffrey R.; Lee, Jennifer A.; Kramp, Tamalee; Kishimoto, Shun; Krishna, Murali C.; Tofilon, Philip; Camphausen, Kevin A.
Abstract : The cover image is based on the Research Article Detection of metabolic change in glioblastoma cells after radiotherapy using hyperpolarized 13 C‐MRI by Tatsuya Kawai et al., https://doi.org/10.1002/nbm.4514 .